509 the people have spoken : (essays on the making of a new Malaysia) - Imran Mohd. Rasid; Chen, Yacai 1961-; Tan, Yvonne; Lim, Jeremy 1973- (Strategic Information and Research Development Centre, 2018)
This book is an anthology of essays recording debates and discourses that took place leading up to the 14th General Election, the historic election that saw a change in power for the first time after more than half a century since Malaysia's Independence. This shift in power that took place on 9 May 2018 opened a new chapter for Malaysians who demand for democratic reform and a transparent trustworthy administration. The voices of the people resounded at the ballot box during this election, demonstrating they are tired of kleptocratic and racial politics practiced by the previous ruling regime. Renewed national aspirations start to emerge and shaping new political organizations are underway for the journey of the people of this country towards a New Malaysia. This book takes us back to examine the sequences of events leading up to GE14. Every essay offers an analysis and recording that captures important moments that should be reflected on and remembered by every Malaysian.